The Humoral Immune Response to HCV: Understanding is Key to Vaccine Development - Cashman, Siobhán B.; Marsden, Brian D.; Dustin, Lynn B. (Frontiers in Immunology, 2014)
Hepatitis C virus (HCV) remains a global problem despite advances in treatment. The low cost and high benefit of vaccines have made them the backbone of modern public health strategies, and the fight against HCV will not be won without an effective vaccine. Achievement of this goal will benefit from a robust understanding of virus-host interactions and protective immunity in HCV infection. In this review we summarise recent findings on HCV-specific antibody responses associated with chronic and spontaneously resolving human infection. In addition, we discuss specific epitopes within HCV’s envelope glycoproteins that are targeted by neutralizing antibodies. Understanding what prompts or prevents a successful immune response leading to viral clearance or persistence is essential to designing a successful vaccine.